Analisis Faktor-Faktor Penentu Loyalitas Konsumen Berdasarkan Customer Loyalty Theory: Studi pada Pengguna Shopee di Pontianak (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the effects of trust, price perception, service quality, promotion, and ease of use on consumer loyalty in Pontianak, with customer satisfaction tested as a mediating variable. Data were gathered quantitatively from 214 active Shopee users aged between 20 and 30 years using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that while service quality and usability only affect satisfaction, price perception, promotion, and trust all have a significant direct impact on loyalty. However, the relationship between these factors and loyalty is not substantially mediated by satisfaction. These results suggest that in transactional e-commerce contexts, loyalty is shaped more by rational drivers such as pricing and promotions than by emotional factors like satisfaction. Practical implications include focusing retention strategies on functional value and direct incentives, while future research may consider alternative models such as Value-Based Loyalty or Behavioral Economics for deeper insights.